2006
DOI: 10.1093/jnci/djj009
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis Based on the Atypical Squamous Cells of Undetermined Significance/Low-Grade Squamous Intraepithelial Lesion Triage Study (ALTS)

Abstract: HPV DNA testing is an economically viable strategy for triage of ASCUS cytology. The less than perfect sensitivity of colposcopy and biopsy needs to be accounted for in future clinical guidelines and policy analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(41 citation statements)
references
References 15 publications
1
37
0
3
Order By: Relevance
“…HPV testing was used to identify the 13 known high-risk HPV types (16,18,31,33,35,39,45,51,52,56,58,59, and 68). Women with abnormal screening results were referred for follow-up colposcopies or repeat screening, and the presence of a cervical lesion was confirmed using colposcopy and biopsy [29][30][31]39,40]. The number of clinic visits varied from 1 to 3 visits, based on screening strategy and test results.…”
Section: Screening Strategies and Diagnostic Follow Upmentioning
confidence: 99%
“…HPV testing was used to identify the 13 known high-risk HPV types (16,18,31,33,35,39,45,51,52,56,58,59, and 68). Women with abnormal screening results were referred for follow-up colposcopies or repeat screening, and the presence of a cervical lesion was confirmed using colposcopy and biopsy [29][30][31]39,40]. The number of clinic visits varied from 1 to 3 visits, based on screening strategy and test results.…”
Section: Screening Strategies and Diagnostic Follow Upmentioning
confidence: 99%
“…21,22 For women with ASCUS, the ALTS trial suggested that the sensitivities of HPV testing and repeat cytology in the detection of CIN3 or worse were similar but that HPV testing (in combination with cytology) would result in fewer referrals to colposcopy, 23 and was considered to be an economically viable strategy. 24 The generalisability of the findings of ALTS is uncertain, particularly to populations in which the prevalence of infection with HPV in women with mild dyskaryosis or LSIL is lower, 4 as reported in the UK. [25][26][27] In a Canadian trial in women with ASCUS or LSIL, addition of HPV testing to repeat cytology resulted in higher sensitivity for detection of CIN2 or worse, but with a substantial loss of specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Repeat cytology examinations were as sensitive as HPV DNA testing for detecting CIN3+, but would require more follow-up visits. Kulasingam et al (2006) conducted a cost-effectiveness analysis of the ALTS trial to determine whether HPV DNA testing is a cost-effective alternative to immediate colposcopy or conservative management (Kulasingam et al, 2006). Their results confirmed that the triage based on a positive HPV DNA test detected more CIN3+ cases and was less costly than immediate colposcopy or conservative management with up to three repeat cytology visits with HSIL+ as the threshold for referral to colposcopy.…”
Section: Discussionmentioning
confidence: 90%